Analysis of Child Development Parenting Patterns in Madras Village (Little India) Medan - Jevera, Ariell; Damanik, Vanny Natalsha; Haro, Diana; Gaol, Katarina Lumban (EDUCTUM: Journal Research, 2024)
This research aims to examine the influence of parenting patterns in Indian culture on children's development in Madras Village (Little India) Medan. This research analyzes how to care for children according to Indian culture, the values and traditions of Indian culture that are passed down and taught to children in life. daily. The research method used is a qualitative method, with data sampling techniques through interviews and documentation. The subjects in this research were housewives living in Madras village, India. In Indian culture, there is a tradition of caring for children from the time they are still in the womb until the child is born. Research also shows that in Indian culture, in raising children, parents instill values or traditions in their children since they are still small. Apart from that, parents also teach Indian languages to their children since they are 4-5 years old. At the age of 4-5 years children are taught Tamil by priests at monasteries or temples.